Factors Affecting the Quality of Primary Special Education Program in Punjab - Kanwal, Asma; Shahid Farooq, Muhammad; Bashir, Rukhsana (JIE, 2025)
People with special needs have long needed additional support to lead healthy, independent lives as valuable members of society. This level of life for people with disabilities may be attained by offering them an education that emphasizes quality education. By recording the opinions of special education teachers, the research sought to investigate the internal key factors that have an impact on the standard of primary special education program. The study's methodology was a quantitative descriptive paradigm. In 14 districts across four zones in the Pakistani state of Punjab, public schools and centers were surveyed using a multistage random sample procedure. A self-developed questionnaire (=.80) was used to gather the data, and statistical methods were used to evaluate the results. Parametric statistical methods were utilised to analyse the data in light of the study's aims. The results showed that the child's disability severity level, classroom management, instructional adaptability, school infrastructure, teacher, administration, and curriculum were the internal elements that had the greatest influence on learning. Based on their professional background and area of expertise, teachers' perceptions of various factors varied from one another. In order to regulate the constituents for better quality special education at the primary level in schools of Punjab, it is necessary to draw the attention of stakeholders to learner health promotion and administrative and professional coordination.